(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Since the early 1990s, India’s engagement with globalization has profoundly reshaped its trade regime, foreign direct investment (FDI) policies, and environmental governance framework. The liberalization reforms initiated in 1991 marked a decisive shift from a tightly controlled and protectionist economic model to a more open, market-oriented system integrated with global trade and capital flows. This transformation coincided with growing international concern regarding environmental degradation, climate change, and sustainable development, placing India at the intersection of competing imperatives of economic growth and ecological protection. The present article critically examines the relationship between trade liberalization, FDI inflows, and environmental regulation in India from 1991 to 2025, with particular emphasis on India’s evolving stance in multilateral trade negotiations, its domestic constitutional and statutory environmental safeguards, and its responses to international environmental agreements. The article argues that while liberalization and FDI have contributed significantly to economic expansion, structural weaknesses—particularly in manufacturing, regulatory enforcement, and environmental compliance—have limited the realization of environmentally sustainable growth. Drawing upon India’s constitutional ethos, traditional ecological values, and contemporary policy initiatives, the study situates India’s environmental trade discourse within broader international debates on equity, globalization, and sustainable development. The analysis concludes that India’s future trajectory depends upon harmonizing trade competitiveness with robust environmental governance, technological innovation, and equitable global cooperation.